Teachers' perception of assessment in early childhood education in Oyo state (2012)
In Early Childhood Education assessment is an issue because of its many roles. To better understand children’s overall development and monitor their progress through the curriculum and as well ientify children who are at risk of academic failure or who may need special education services, and for us to assess the value or worth of the programme, assessment is essential. All these enormous roles are enough rationale for child educators to have right perception of assessment in early childhood education. This study examined teachers’ perception of assessment in early childhood education. Descriptive survey method was adopted. Three research questions were answered and two hypotheses were formulated and tested at 0.05 level of significance. Two hundred ZOO) early childhood education teachers from both urban and rural were involved in the study. Teachers' Perception of Assessment Questionnaire (TPAQ) was used to collect data. Data collected were analyzed through tables, frequency counts, percentages and mean rating statistical techniques. Results show that the early childhood teachers do not have right perception of assessment in early childhood education and that the predominant method of assessment among them is paper and pencil. Therefore, the study recommended that teacher preparation programmes should include courses in assessment and child observation, and teachers already in the classroom should be trained in the use of purposeful observation, documentation, and analysis of assessment data,